2018
DOI: 10.1021/acsomega.8b02279
|View full text |Cite
|
Sign up to set email alerts
|

Reusable Functionalized Hydrogel Sorbents for Removing Long- and Short-Chain Perfluoroalkyl Acids (PFAAs) and GenX from Aqueous Solution

Abstract: Per- and poly-fluoroalkyl substances (PFASs) are man-made chemicals that are toxic and widely detected in the environment, including drinking water sources. A cost-effective treatment process for PFASs is currently not available. We developed reusable hydrogel sorbents to remove long- and short-chain perfluoroalkyl acids and 2,3,3,3-tetrafluoro-2-(heptafluoropropoxy)propanoic acid (GenX), which is are emerging PFAS. Through fluoridation and amination of poly(ethylene glycol) diacrylate (PEGDA), the newly synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…[27-30, 32, 34, 35] Many emerging PFAS remediation technologies have demonstrated efficient PFAS removal in batch studies conducted in pure water at low to moderate PFAS concentrations, but few have been studied in real water matrices or in flow-through columns. In general, emerging PFAS remediation technologies leverage intermolecular interactions such as ion exchange, [36][37][38][39][40] hydrophobic or fluorous interactions, [39][40][41][42][43][44][45] or encapsulation by supramolecular receptors [46][47][48][49][50][51][52] to bind PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…[27-30, 32, 34, 35] Many emerging PFAS remediation technologies have demonstrated efficient PFAS removal in batch studies conducted in pure water at low to moderate PFAS concentrations, but few have been studied in real water matrices or in flow-through columns. In general, emerging PFAS remediation technologies leverage intermolecular interactions such as ion exchange, [36][37][38][39][40] hydrophobic or fluorous interactions, [39][40][41][42][43][44][45] or encapsulation by supramolecular receptors [46][47][48][49][50][51][52] to bind PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…Current and emerging PFAS remediation technologies typically remove waterborne contaminants nonspecifically, resulting in saturation by nonfluorinated species. , For example, current PFAS remediation efforts using granular activated carbon (GAC) demonstrate substantial breakthrough at modest treatment volumes for short-chain PFASs . Furthermore, the binding affinities of organic contaminants to GAC are often higher than those of PFASs, which can result in PFASs leaching into filtered water over time. , Emerging technologies include porous organic polymer adsorbents and ion exchange materials that contain a fluorinated component. While these materials show great promise for adsorbing long-chain PFASs, they are still at an early stage of development, have generally not been tested in real water, and/or display modest selectivity for short-chain PFASs.…”
mentioning
confidence: 99%
“…However, the removal efficiency for short-chain species PFHxA increased by ∼74% through exploiting the dual-recognition mechanism. Other bifunctional hydrogel-based PFAS sorbents developed by Huang et al 136 and Kumarasamy et al ( Figure 7 b) 38 also indicated an enhancement in adsorption affinity toward PFAS when fluorous probes and cationic probes are combined compared to that of single-type probes. The interplay between hydrophobic and ionic interactions was studied by Zhang et al 137 by modifying the surface of Fe 3 O 4 /SiO 2 nanoparticles with mixed groups of octadecyltriethoxysilane (ODS) and aminopropyltrimethoxysilane (APTMS), which are a long alkyl chain and a short alkyl chain terminated with the amine group, respectively ( Figure 7 c).…”
Section: Selectivity Toward Pfasmentioning
confidence: 80%